Transatlantic aliens : modernism, exile, and culture in midcentury America - Norman, Will, 1978- (Hopkins studies in modernism., 2016)
"This book is about how a set of European writers, intellectuals, and artists encountered and negotiated American culture in the mid-twentieth century. The "Intellectual Migration" of the 1930s and '40s has long been recognized as one of the most important moments in twentieth-century cultural history, but it has often been narrowly understood as a clash between a rarefied European modernist sensibility and a debased American mass culture. Transatlantic Aliens adopts a more capacious understanding of this encounter as a pivotal crisis point for modernism and culture more broadly, one at which claims for the autonomy of high culture became increasingly untenable, the geographical center of cultural authority was displaced, and the governing principles of the American cultural field went through a phase of dramatic instability. Transatlantic Aliens takes the form of a series of interlinked case studies, each addressing individual or paired transatlantic figures, from C.L.R. James and Simone de Beauvoir to George Grosz and Vladimir Nabokov. Detailed attention to individual artworks, novels, and works of criticism is combined with more distant readings that seek to understand their function within larger intellectual histories and cultural formations, spanning time and space. The objective in each case is to explore what the transatlantic trajectories of particular figures tell us not only about the development of their own practices but also about the fate of European high culture in the American century"--